Ask questions, share knowledge, and connect with a vibrant community on IDNLearn.com. Find in-depth and accurate answers to all your questions from our knowledgeable and dedicated community members.
Sagot :
To find [tex]\( a_4 \)[/tex] using the given recursive formula [tex]\( a_n = 3a_{n-1} - 10 \)[/tex] with the initial term [tex]\( a_1 = 7 \)[/tex], we will calculate the terms of the sequence step-by-step.
1. Calculate [tex]\( a_2 \)[/tex]
[tex]\[ a_2 = 3a_1 - 10 \][/tex]
Substitute [tex]\( a_1 = 7 \)[/tex]:
[tex]\[ a_2 = 3 \times 7 - 10 = 21 - 10 = 11 \][/tex]
2. Calculate [tex]\( a_3 \)[/tex]
[tex]\[ a_3 = 3a_2 - 10 \][/tex]
Substitute [tex]\( a_2 = 11 \)[/tex]:
[tex]\[ a_3 = 3 \times 11 - 10 = 33 - 10 = 23 \][/tex]
3. Calculate [tex]\( a_4 \)[/tex]
[tex]\[ a_4 = 3a_3 - 10 \][/tex]
Substitute [tex]\( a_3 = 23 \)[/tex]:
[tex]\[ a_4 = 3 \times 23 - 10 = 69 - 10 = 59 \][/tex]
Therefore, the value of [tex]\( a_4 \)[/tex] is [tex]\( \boxed{59} \)[/tex].
1. Calculate [tex]\( a_2 \)[/tex]
[tex]\[ a_2 = 3a_1 - 10 \][/tex]
Substitute [tex]\( a_1 = 7 \)[/tex]:
[tex]\[ a_2 = 3 \times 7 - 10 = 21 - 10 = 11 \][/tex]
2. Calculate [tex]\( a_3 \)[/tex]
[tex]\[ a_3 = 3a_2 - 10 \][/tex]
Substitute [tex]\( a_2 = 11 \)[/tex]:
[tex]\[ a_3 = 3 \times 11 - 10 = 33 - 10 = 23 \][/tex]
3. Calculate [tex]\( a_4 \)[/tex]
[tex]\[ a_4 = 3a_3 - 10 \][/tex]
Substitute [tex]\( a_3 = 23 \)[/tex]:
[tex]\[ a_4 = 3 \times 23 - 10 = 69 - 10 = 59 \][/tex]
Therefore, the value of [tex]\( a_4 \)[/tex] is [tex]\( \boxed{59} \)[/tex].
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is committed to providing the best answers. Thank you for visiting, and see you next time for more solutions.